Incense and Islam in Indonesian context: An ethnobotanical study - Royyani, Mohammad F.; Keim, Ary P.; Efendy, Oscar; Imadudin, Iim; Mahmud, M. Irfan; Sy, Pahmi; Setyawati, Titiek; Nuralia, Lia; Hidayat, Asep; Sujarwo, Wawan (Ethnobotany Research and Applications, 2024)
in which the resins are burned to produce fragrant fumes. The study aims to understand the arrival and development of Islam in Indonesia, which is apparently brought by the Muslim traders with good understanding of Sufism. In order to achieve the high level of enlightenment, the Sufis need medium in the form of incense. Methods: Ethnohistorical approach was used in this study by combining historical events from an anthropological perspective with data collected in the form of literature review and supporting documents. Results: The study revealed that the Arabs have interacted with incense from Indonesia since the pre Islamic time mainly the so called Indonesian incenses, such as Sumatran incense or kemenyan (Styrax benzoin Dryand., and Styrax sumatranus J.J.Sm.), Sumatran camphor (Dryobalanops aromatica C.F.Gaertn.), agarwood (Aquilaria malaccensis Lam.), and sandalwood (Santalum album L.). Conclusions: The traders from Indonesia came to the Southern Arabia (particularly Hadhramaut in Yemen) to trade the valuable spices. When Islam came to Southern Arabia, the people of Indonesia might learn Islam there and brought back to Indonesia prior to the coming of the Muslim teachers from Arabia. Indonesia, i.e., Sundaland, has been recognized as the area that produces the best known incenses since the Late Pleistocene. Incense has been an integral part of the Austronesian (including Indonesian) civilization and societies; thus both cannot be separated. Keywords: Ethnobotany; Incense; Indonesia; Islam